IL-6 Improves the Nitric Oxide-Induced Cytotoxic CD8+ T Cell Dysfunction in Human Chagas Disease - Sanmarco, Liliana Maria; Visconti, Laura Marina; Eberhardt, Natalia; Ramello, Maria Cecilia; Ponce, Nicolás Eric; Spitale, Natalia Beatriz; Vozza, Maria Lola; Bernardi, Germán Andrés; Gea, Susana; Minguez, Angel Ramón; Aoki, Maria Pilar (Frontiers in Immunology, 2016)
Reactive oxygen and nitrogen species are important microbicidal agents but are also involved in lymphocyte unresponsiveness during experimental infections. Many of the biological effects attributed to nitric oxide are mediated by peroxynitrites, which induce the nitration of immune cells, among others. Our group has demonstrated that nitric oxide is involved in the suppressive activity of myeloid-derived suppressor cells in T. cruzi-infected mice, with a higher number of CD8+ T cells suffering surface-nitration compared to uninfected controls. Studying the functional and phenotypic features of peripheral CD8+ T cells from chagasic patients and human cells experimentally infected with T. cruzi, we found that different regulatory mechanisms impaired the effector functions of T cytotoxic population from seropositive patients. Peripheral leukocytes from chagasic patients showed increased nitric oxide production concomitant with increased tyrosine nitration of CD8+ T cells. Additionally, this cytotoxic population exhibited increased apoptotic rate, loss of the TCR ζ-chain and lower levels of CD107a, a marker of degranulation. Strikingly, IL-6 stimulation of in vitro infected peripheral blood mononuclear cells obtained from healthy donors, blunted T.cruzi-induced nitration of CD3+CD8+ cells and increased their survival. Furthermore, the treatment of these cultures with an IL-6 neutralizing antibody increased the percentage of T. cruzi-induced CD8+ T cell nitration and raised the release of nitric oxide. The results suggest that the under-responsiveness of cytotoxic T cell population observed in the setting of long-term constant activation of the immune system could be reverted by the pleiotropic actions of IL-6, since this cytokine improves its survival and effector functions.